Development of an Operating Room Nursing Workload Measurement System - Friedberg, Elaine; O'Reilly, Lila; Theriault, Jo-Ann (Operating Room Nurses Association of Canada Journal, 1992)
After the Ottawa General Hospital became one of the test sites for the Canadian MIS Project in 1985, We began to introduce retrospective “Workload Measure- ment Systems” (WLMS) in nursing and diagnostic service departments. At this time Specialty unit WLM systems, inclusive of the Operating Room system, were in developmental stages. We decided to proceed with the systems implementation program, assuring compliance with retrospective requirements.